PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN BOLAANG MONGONDOW SELATAN - Olvie Nanda Sasue; Grace A. J. Rumagit; Mex L. Sondakh (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the role of the agricultural sector to the economy of South Bolaang Mongondow Regency and its development in the period of 5 years ie in 2010 until 2014 and also to know the agricultural sector is the base or non-base sector. The data used is secondary data. This secondary data is obtained from the relevant agencies namely the Central Bureau of Statistics of North Sulawesi Province. The data is then analyzed using contribution formulas, growth formula and Location Quotient (LQ) analysis. The results showed that the agricultural sector is the largest contributor to the economy of Bolaang Mongondow Selatan Regency. This can be seen from the calculation of contribution and development of agricultural sector contribution to South Bolaang Mongondow Regency PDRB from 2010 to 2014. Based on the results of research also known that the development of agriculture sector to PDRB shows an increase that is from 2010-2014 with the largest increase occurred in 2013 with growth reached 5.82%, this can be interpreted that the productivity of agricultural sector in South Bolaang Mongondow Regency is good. From the analysis result using LQ, it can be seen that agriculture sector is base sector in South Bolaang Mongondow Regency, it means the role of agricultural sector in Bolaang Mongondow Selatan Regency is bigger.